Reducing carbon emission by visiting patients activities in a screening centre through cleaner production strategies / Mohd Firdaus Bakri - Mohd Firdaus , Bakri (2017)
In this work, a cleaner production strategy was conducted in HSC (Heart, Stroke, Cancer) Medical Center, located in Ampang, Kuala Lumpur with an objective to propose improvement opportunities to reduce carbon emission generated from resources consumption and waste generated from medical treatment activities. For this purpose, a detailed cleaner production audit was conducted to identify key entities that contributed to the generation of carbon emission in the case studied medical center. The boundary of study covers activities related with medical treatment of patients. The stage involved is from the moment patient start to register at until they finished all their examination tests. The CP audit conducted focusing on waste minimization, energy efficiency as well as water minimization. Since global warming issues is currently a hot topic which affect the ecosystem and become a threat to nature living, this study has been justified through CO2 equivalent emission before and after CP implementation. The objective of this study is to generate potential cleaner production options that can be suited best for the premise. Total carbon foot print quantity will be judged along the study based on the costing analysis is carried out. Health issue related to the process emission has also been included in this study as it constitutes part of the major process. Method of data collection has been obtaining through past records, observation and feedback from personnel. CP option were then generated and evaluated to identify the feasibility of implementation. Cleaner production audit findings shows that 207 tonnes of CO2 was generated annually from overall activities in the hospital where the main contributors of the carbon emission generation were electricity, water consumption and waste management, with percentage of contribution of 83.5%, 15%, 1.70% respectively. Subsequently nine CP option were generated. Focusing on electricity, water consumption, and waste management. The implementation of the options can save up to RM3660 per month. Furthermore, the implementation also is expected to improve other aspect, such as reduction in safety risk aspect, increase in productivity, and uphold the company image. The results from this work show that CP strategies can be implemented in many sectors, including service sectors such as hospital to reduce carbon emission on a national level as well as on a scale of global uptakes.